The Influence of Rupiah Exchange Rate Fluctuations (KURS) on Share Price Movements in Manufacturing Companies on the Indonesian Stock Exchange - Prameswary, Nur Safitri (Journal of Business Inflation Management and Accounting, 2024)
This research is intended to determine the effect of exchange rate fluctuations on stock price movements of manufacturing companies on the IDX. The sample is the rupiah exchange rate and stock prices in 2009. The data analysis technique used is simple linear regression analysis. The results of this research show that appreciation of the rupiah exchange rate has a positive relationship with stock prices in manufacturing companies on the Indonesia Stock Exchange.